Tracking the evolution of the bacterial choline-binding domain: molecular characterization of the Clostridium acetobutylicum NCIB 8052 cspA gene. - Sanchez-Beato, A R (1995)
The major secreted protein of Clostridium acetobutylicum NCIB 8052, a choline-containing strain, is CspA (clostridial secreted protein). It appears to be a 115,000-M(r) glycoprotein that specifically recognizes the choline residues of the cell wall. Polyclonal antibodies raised against CspA detected the presence of the protein in the cell envelope and in the culture medium. The soluble CspA protein has been purified, and an oligonucleotide probe, prepared from the determined N-terminal sequence, has been used to clone the cspA gene which encodes a protein with 590 amino acids and an M(r) of 63,740. According to the predicted amino acid sequence, CspA is synthesized with an N-terminal segment of 26 amino acids characteristic of prokaryotic signal peptides. Expression of the cspA gene in Escherichia coli led to the production of a major anti-CspA-labeled protein of 80,000 Da which was purified by affinity chromatography on DEAE-cellulose. A comparison of CspA with other proteins in the EMBL database revealed that the C-terminal half of CspA is homologous to the choline-binding domains of the major pneumococcal autolysin (LytA amidase), the pneumococcal antigen PspA, and other cell wall-lytic enzymes of pneumococcal phages. This region, which is constructed of four repeating motifs, also displays a high similarity with the glucan-binding domains of several streptococcal glycosyltransferases and the toxins of Clostridium difficile.